2011
DOI: 10.1578/am.37.2.2011.161
|View full text |Cite
|
Sign up to set email alerts
|

Foramen Ovale and Ductus Arteriosus Patency in Neonatal Harbor Seal (Phoca vitulina) Pups in Rehabilitation

Abstract: Twenty neonatal harbor seal (Phoca vitulina) pups in rehabilitation following maternal separation underwent serial echocardiographic studies to assess patency and subsequent age of functional closure of the ductus arteriosus (d.a.). B-mode, color-flow Doppler, and pulse and continuous wave Doppler were utilized to identify the d.a. and determine patency and directionality of blood flow. Seals were also evaluated for evidence of foramen ovale (f.o.) patency. B-mode ultrasound was used to evaluate the inter-atri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…There is parenchymal collapse, neuronal loss throughout the dentate gyrus (DG) and cornu ammonis (CA) sectors 1-4, and gliosis. may be functional patency of the foramen ovale and ductus arteriosus up to 6-7 weeks of age, therefore, these should not be considered congenital defects in very young pups without additional evidence of cardiac disease ( Dennison et al, 2011). In elephant seals, hydrocephalus and cardiac abnormalities are most common.…”
Section: Figure 234 Chronic Lesions Of Domoic Acid Toxicosis In the mentioning
confidence: 99%
“…There is parenchymal collapse, neuronal loss throughout the dentate gyrus (DG) and cornu ammonis (CA) sectors 1-4, and gliosis. may be functional patency of the foramen ovale and ductus arteriosus up to 6-7 weeks of age, therefore, these should not be considered congenital defects in very young pups without additional evidence of cardiac disease ( Dennison et al, 2011). In elephant seals, hydrocephalus and cardiac abnormalities are most common.…”
Section: Figure 234 Chronic Lesions Of Domoic Acid Toxicosis In the mentioning
confidence: 99%
“…Cardiac abnormalities and diseases have been reported postmortem in marine mammals such as northern elephant seals (Mirounga angustirostris), pygmy sperm whales (Kogia breviceps), bottlenose dolphins (Tursiops truncatus), northern fur seals (Callorhinus ursinus), dwarf sperm whales (Kogia sima), Florida manatees (Trichechus manatus latirostris), and southern sea otters (Enhydra lutris) (Trupkiewicz et al, 1997;Kreuder et al, 2003;Bossart et al, 2007;Powell et al, 2009;Spraker & Lander, 2010;Gerlach et al, 2013). Only a few studies have achieved the in vivo diagnosis of heart abnormalities in marine mammals through echocardiography such as the foramen ovale and ductus arteriosus patency found in neonatal harbor seals (Phoca vitulina; Dennison et al, 2011a) or the ventricular septal defects found in a harbor porpoise (Phocoena phocoena; Szatmári et al, 2016) and California sea lions (Zalophus californianus; Dennison et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…Several heart defects were noted, including a ventricular septal defect, mitral valvular dysplasia with associated hydrothorax, myocardial fibrosis, and mitral valvular thickening. Patent foramen ovale were noted in two weaned pups and one yearling, animals older than expected for persistent fetal circulation (Dennison et al 2011).…”
mentioning
confidence: 81%